1988
DOI: 10.1111/j.1574-6968.1988.tb03141.x
|View full text |Cite
|
Sign up to set email alerts
|

Methods for the identification and analysis of l-altrose in bacterial polysaccharides

Abstract: Methods for the detection, quantitation, and configurational analysis of altrose in bacterial polysaccharides were developed and are described. Thin layer chromatography (TLC) is first used to qualitatively detect altrose and other monosaccharides in polysaccharide hydrolysates. Alditol acetates are then prepared from these hydrolysates and analyzed by either gas‐liquid chromatography (GLC) or GLC‐mass spectroscopy (GLC‐MS), depending on the nature of the constituent sugars. These data allow the calculation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…EPs from several strains have been characterized on the basis of sugar composition (20). The compositional analysis of EPs produced by 37 strains of B. fibrisolvens showed that unusual sugars such as L-altrose (19,21), 4-O-(1-carboxyethyl)-D-galactose (23), and 4-O-(1-carboxyethyl)-L-rhamnose (24) are common constituents of the EPs. However, the rheological and functional properties of these EPs have not been studied.…”
mentioning
confidence: 99%
“…EPs from several strains have been characterized on the basis of sugar composition (20). The compositional analysis of EPs produced by 37 strains of B. fibrisolvens showed that unusual sugars such as L-altrose (19,21), 4-O-(1-carboxyethyl)-D-galactose (23), and 4-O-(1-carboxyethyl)-L-rhamnose (24) are common constituents of the EPs. However, the rheological and functional properties of these EPs have not been studied.…”
mentioning
confidence: 99%
“…As it is shown in Table 2, the monosaccharide composition of glycosyl derivatives of the hydrolysed bioemulsifier consisted of 36AE6% glucose, 8AE1% galactose, 30AE9% altrose and 24AE4% mannose in molar ratio, which appeared to be variably composed from that of bioemulsifiers reported previously (Rougeaux et al 1998;Singh et al 2011) except for altrose, which was identified in some microbial extracellular polysaccharides (Stack 1987;Stack and Ericsson 1988). GC-MS analysis of lipidic fraction showed that hexadecanoic acid and octadecanoic acid were the major fatty acids that account for 94AE4% of total fatty acids.…”
Section: Characterization Of the Bioemulsifiermentioning
confidence: 97%
“…The unusual sugars identified in the EPSs made by B. fibrisolvens consist of both neutral and acidic types. For example, L-altrose was first reported in nature as a major component of the EPS made by strain CF3 [3], and was then subsequently found in the EPS from many additional strains [1,4]. Of the two different EPSs made by strain X6C61, one contained 6-deoxy-Dtalose [5] whereas the other contained L-iduronic acid [6].…”
Section: Introductionmentioning
confidence: 99%
“…spectra of 78.2 alditol acetates prepared from d2-NS-B. 16.9The structural elucidation of 4-0-(l-carboxyethyl)-L-rham-65 4.…”
mentioning
confidence: 99%